Examining The Use of Evaluative Evidence in Decision- Making Within Catholic Faith-Based Organisations - Ebong, Fotoh Paul (University of the Witswatersrand, Johannesburg, 2023)
Catholic Faith-Based Organisations are critical in contributing to social betterment through various development initiatives(Camilleri & Winkworth, 2004). The use of evaluations conducted in these organisations to enhance learning, programme improvement and eventually social betterment through informed decision-making is the concern of this research. Literature on the use of evaluations underlines the fact that evaluations are aimed at providing relevant information to various stakeholders for their decision-making and improvement of the evaluand as well as assessing their merits and worth (Alkin, 1975; Maloney, 2017a; Patton, 2012; Stufflebeam, 2001a). As a widely researched phenomenon, the use of evaluation has been identified by various authors to include instrumental use, conceptual use, process use, and symbolic use (Alkin & Christie, 2004; Johnson et al., 2009). The need to make evaluations useful has, therefore, been the driving force behind the development of the different approaches to evaluation, evaluation principles and standards, as well as the creation of various voluntary associations to sustain and promote the professionalism of the field (Stufflebeam, 2004). Even though Catholic faith-based organisations conduct evaluations, little is documented about the extent to which these evaluations were used in decision-making processes, if any, and what role the evaluation characteristic factors, organisational and human factors play in influencing use. To investigate the extent to which these organisations use these evaluations and the extent to which evaluation distinct variables play a role in enhancing use, a mixed method was undertaken to gather quantitative and qualitative data from 43 respondents who were selected purposefully among the eligible organisations for the study. A questionnaire was administered online, followed by key informant interviews. The findings show that most organisations make use of evaluations to inform practice. Still, since the evaluations are commissioned mainly by the funders, the willingness of these organisations to take the initiative of conducting their evaluations is less evident. To some, carrying out evaluations is merely to comply with the funding requirements rather than seeking evidence based upon which informed decisions can be made. Therefore, I recommend that Catholic faith-based organisations institutionalise monitoring and evaluation units within their organisations to strengthen their internal capacity to generate and use evidence in decision-making. This would equally build evidence-use awareness and establish a culture of evaluative thinking in organisational practices.
A research report submitted to the Faculty of Law, Commerce, and Management of the University of the Witwatersrand, in partial fulfilment for the degree of Master of Management in Public and Development Sector Monitoring and Evaluation.
Keywords: Evaluative Evidence; Decision- Making; Catholic Faith-Based Organisations; Programme improvement; Social betterment; SDG-16: Peace, justice and strong institutions